FINAL HEIGHT AND ENDORINE COMPLICATIONS IN PATIENTS WITH β-THALASSSEMIA INTERMEDIA: OUR EXPERIENCE IN NON-TRANSFUSED VERSUS INFREQUENTLY TRANSFUSED PATIENTS AND CORRELATIONS WITH LIVER IRON CONTENT - Vincenzo De Sanctis; Mohamed Yassin (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract. Backgrond: β-thalassemia intermedia (TI) spans a wide spectrum of severity and carries higher morbidity than previously recognized, including extramedullary hematopoeisis, leg ulcers, gallstones, thrombosis, secondary heart failure, pulmonary hypertension, skeletal deformity, growth retardation and endocrine abnormalities, such as diabetes mellitus, hypothyroidism, osteoporosis, and hypogonadism.